2011
DOI: 10.1016/j.jcrs.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic pupil dilation as a predictive test for the risk for intraoperative floppy-iris syndrome

Abstract: PURPOSE:To evaluate the effect of a1-adrenergic receptor antagonists (a1-ARAs) on pupil diameter and determine whether the diameter predicts intraoperative floppy-iris syndrome (IFIS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
(72 reference statements)
2
32
0
3
Order By: Relevance
“…These findings are consistent with the fact that patients with tamsulosin treatment develop progressive intraoperative pupillary miosis during cataract surgery [2,3,10]. In contrast, Casuccio et al found that pupil diameter was significantly smaller both preoperatively and postopoperatively in patients taking tamsulosin compared with their control group, however both exclusion criteria and their mydriatic regimen were different [27]. …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings are consistent with the fact that patients with tamsulosin treatment develop progressive intraoperative pupillary miosis during cataract surgery [2,3,10]. In contrast, Casuccio et al found that pupil diameter was significantly smaller both preoperatively and postopoperatively in patients taking tamsulosin compared with their control group, however both exclusion criteria and their mydriatic regimen were different [27]. …”
Section: Discussionsupporting
confidence: 74%
“…History of tamsulosin use among patients undergoing cataract surgery was estimated around 3% in the United States [25-27]. Although several pre- and intraoperative methods are used to overcome this problem, IFIS remains one of the pitfalls of cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Casuccio et al prospectively grouped 150 patients into 3 equally distributed groups: 1 taking tamsulosin for at least a year, 1 taking another a 1A -ARA for at least a year, and a control group never on a a 1A -ARA. 12 In the tamsulosin group, 29 cases (58%) of IFIS were identified. Using a pupillary dilation cutoff of 7 mm, IFIS was able to be predicted with a 73% sensitivity and a 95% specificity (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies demonstrated an increased risk of IFIS with pupil dilation of < 6.5 or 7 mm, respectively. 12,13 The purpose of our study was to determine if a pharmacological test could be developed to determine iris dysfunction in patients taking tamsulosin, by isolating the selective adrenergic effects of 2.5% phenylephrine. We further examined if there exists a progression of smooth muscle dysfunction with duration of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Less than full pupillary dilatation is also good predictive factor for IFIS (Casuccio et al 2011); therefore, we aimed to select for the study patients with less than full pupillary dilatation on the preoperative assessment.…”
Section: Discussionmentioning
confidence: 99%